ANALISIS STRATEGI PENGEMBANGAN USAHA MENGGUNAKAN METODE QUANTITATIVE STRATEGIC PLANNING MATRIX (QSPM) PADA PETERNAKAN AYAM PEDAGING CV CIPTA SAMA ABADI - Alfandy Cristian Debataraja, (2023)
CV Cipta Sama Abadi is a poultry farm established in 2020 and specifically focuses on the rearing of broiler chickens. CV Cipta Sama Abadi's poultry farm has an existing business management strategy, which involves purchasing the same quantity of chicks, 10,000, in each period. The farm faces challenges related to a fluctuating market with unpredictable selling prices and the mortality of chicks, which can reduce profits. The objective of this research is to address the challenges faced by CV Cipta Sama Abadi by formulating a business development strategy through the evaluation of internal and external factors affecting the company. The research methodology employed includes the use of the IFE matrix, EFE matrix, IE matrix, SWOT matrix, and QSPM. The analysis using the IE matrix reveals that CV Cipta Sama Abadi poultry farm falls into quadrant II with growth and build strategy. The SWOT analysis generates five alternative strategies. In the QSPM calculation, a comparison is made between the proposed strategies and the existing ones, and it is found that the value of the existing strategy is lower than that of the proposed strategy.